iTRAQ-Based Comparative Proteomic Analysis of Acinetobacter baylyi ADP1 Under DNA Damage in Relation to Different Carbon Sources - Jiang, Bo; Xing, Yi; Li, Guanghe; Zhang, Nana; Lian, Luning; Sun, Guangdong; Zhang, Dayi (Frontiers in Microbiology, 2020)
DNA damage response allows microorganisms to repair or bypass DNA damage and maintain the genome integrity. It has attracted increasing attentions but the underlying influential factors affecting DNA damage response are still unclear. In this work, isobaric tags for relative and absolute quantification (iTRAQ) based proteomic analysis was used to investigate the influence of carbon sources on the translational response of Acinetobacter baylyi ADP1 to DNA damage. After cultivated in a nutrient-rich medium (LB) and defined media supplemented with four different carbon sources (acetate, citrate, pyruvate and succinate), a total of 2,807 proteins were identified. Among them, 84 proteins involved in stress response were significantly altered, indicating the strong influence of carbon source on the response of A. baylyi ADP1 to DNA damage and other stresses. As the first study on the comparative global proteomic changes in A. baylyi ADP1 under DNA damage across nutritional environments, our findings revealed that DNA damage response in A. baylyi ADP1 at translational level is significantly altered by carbon source, providing an insight into the complex protein interactions across carbon sources and offering theoretical clues for further study to elucidate their general regulatory mechanism to adapt to different nutrient environments.